A theoretical simulation of small-molecules sensing on an S-vacancy SnS2 monolayer. Issue 16 (6th April 2017) - Zhao, Rumeng; Wang, Tianxing; Zhao, Mingyu; Xia, Congxin; Zhao, Xu; An, Yipeng; Dai, Xianqi
Abstract : Using first-principle atomistic simulations, we focused on the electronic structures of small gas molecules (CO, H2 O, NH3, NO, and NO2 ) adsorbed on the S-vacancy SnS2 monolayer. Abstract : Using first-principle atomistic simulations, we focused on the electronic structures of small gas molecules (CO, H2 O, NH3, NO, and NO2 ) adsorbed on the S-vacancy SnS2 monolayer. The results show that H2 O and CO molecules were physisorbed on the S-vacancy SnS2 monolayer, whereas NH3, NO, and NO2 molecules were chemisorbed on the S-vacancy SnS2 monolayer via strong covalent bonds. Moreover, our calculations show that H2 O and NH3 act as charge donors, whereas CO, NO, and NO2 gas molecules act as acceptors. Different adsorption behaviors of common gas molecules on the S-vacancy SnS2 monolayer provide a feasible way to exploit chemical gas sensors and electrical devices. In particular, our results also show that under applied biaxial strains, the adsorption energy and charge transfer of gas molecules on the S-vacancy SnS2 monolayer dramatically changed, which indicates that external factors on the S-vacancy SnS2 monolayer are highly preferred.